ChemInform Abstract: A Cascade Synthetic Route to New Bioactive Spiroindolinepyrido[1, 2‐a]indolediones from Indirubin. Issue 8 (February 2016) - Sele, Alexander M.; Bremner, John B.; Willis, Anthony C.; Haritakun, Rachada; Griffith, Renate; Keller, Paul A.
Abstract: Derivative (Vb) shows promising activity against three different cancer cell lines.